Identification of key genes involved in catechin metabolism in tea seedlings based on transcriptomic and HPLC analysis - Zhang, Yazhen; Wei, Kang; Li, Hailin; Wang, Liyuan; Ruan, Li; Pang, Dandan; Cheng, Hao
Tea is a non-alcoholic beverage with many benefits to human health and thereby widely consumed in the world. It contains plenty of secondary metabolites and tea catechins are the characteristic compounds. To further elucidate the biosynthetic and regulatory mechanisms of catechins in tea, high performance liquid chromatography (HPLC)and transcriptome analysis were performed in tea seedlings of different growth stages. A combined method of differential expression and correlation analysis was then conducted. The results showed that the order of total catechin (TC)contents was leaves > stems > roots, irrespective of growth stages. For transcriptome analysis, a total of 355.81 million clean reads were generated and mapped to the referencing tea genome. Further real time PCR analysis of 18 selected genes confirmed RNA-Seq results. A total of 7 structural genes and 35 transcription factors (TFs)were identified to be significantly correlated with TC changes. Among them, three TFs homologous toANL2,WRKY44andAtMYB113 might play key roles in catechin regulation. The de novotranscriptome data of different organs in tea seedlings provided new insights into the biosynthetic and metabolic pathways of catechins.
Keywords: CAMELLIA SINENSIS; CORRELATION ANALYSIS; TRANSCRIPTOME ANALYSIS; CATECHIN BIOSYNTHESIS; TRANSCRIPTION FACTOR